2015
DOI: 10.1128/aac.00098-15
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver and Titanium Dioxide Nanoparticles Using Euphorbia prostrata Extract Shows Shift from Apoptosis to G 0 /G 1 Arrest followed by Necrotic Cell Death in Leishmania donovani

Abstract: The aim of the present study was to synthesize silver (Ag) and titanium dioxide (TiO 2 ) nanoparticles (NPs) using green synthesis from aqueous leaf extract of Euphorbia prostrata as antileishmanial agents and to explore the underlying molecular mechanism of induced cell death. In vitro antileishmanial activity of synthesized NPs was tested against promastigotes of Leishmania donovani by alamarBlue and propidium iodide uptake assays. Antileishmanial activity of synthesized NPs on intracellular amastigotes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(61 citation statements)
references
References 49 publications
3
58
0
Order By: Relevance
“… reported the strong association of the relative percentage amount of each component in GC/MS with the ratio of their average peak area to the total area. Several other bioactive compounds, such as 2,3‐dihydrobenzofuran and 3,4‐dimethylbenzamide containing N─H functional groups, may also contribute to reducing gold ions and stabilizing AuNPs, as reported in previous studies conducted on the synthesis of nanoparticles . Therefore, these Py–GC/MS findings disclosed the possible involvement of polyphenolic compounds along with benzofurans and amides in bioreduction of Au +3 and stabilization of AuNPs.…”
Section: Resultssupporting
confidence: 73%
“… reported the strong association of the relative percentage amount of each component in GC/MS with the ratio of their average peak area to the total area. Several other bioactive compounds, such as 2,3‐dihydrobenzofuran and 3,4‐dimethylbenzamide containing N─H functional groups, may also contribute to reducing gold ions and stabilizing AuNPs, as reported in previous studies conducted on the synthesis of nanoparticles . Therefore, these Py–GC/MS findings disclosed the possible involvement of polyphenolic compounds along with benzofurans and amides in bioreduction of Au +3 and stabilization of AuNPs.…”
Section: Resultssupporting
confidence: 73%
“…This biogenic nanoparticles offered parasitic activity against Leishmania donovani with a IC 50 value of 3.89 and 14.94 mg ml À1 in amastigotes and promastigotes stage. 237 Similar study by Ahmad et al reported promising antileishmanial activity (IC 50 value 4.37) of green synthesized spherical AgNPs (3-8 nm) using phytochemicals from Sargentodoxa cuneata. 238 Lopes et al reported that green synthesized AgNPs using tannic acid (TA) officered antileishmanial activity.…”
Section: Green Synthesized Silver Nanoparticles Against Leishmaniamentioning
confidence: 56%
“…Antioxidant activity of EO may be beneficial for the antileishmanial activity of the plant metabolites. It was reported previously by Zahir et al, 2015 [50], that induced decrease of reactive oxygen species level by Euphorbia plant extract is implicated in the death mechanism of Leishmania parasites and could be responsible for the caspase-independent shift from apoptosis to massive necrosis. Furthermore, studies done previously by our team [51] have shown that increase in reactive oxygen species induced by Leishmania Eukaryotic Initiation Factor (LeIF) in murine macrophages is implicated in the enhancing resistance of macrophages J774 to Leishmania infection.…”
Section: Discussionmentioning
confidence: 98%